Digital transformation in engineering management : case studies of digital transformation in Africa (Emerald Publishing Limited, 2025)
Digital Transformation in Engineering Management presents a collection of real-world case studies providing insights into the innovative ways that digitalisation is transforming companies, enhancing their efficiency and improving sustainability. The book spans multiple industries and offers a unique perspective on current trends and challenges presented by digital transformation. This book is an essential resource for those interested in understanding the transformative power of digital innovation. It covers a diverse range of sectors, including water, steel, energy and mining, and incorporates key lessons from other sectors. Encompassing small and medium enterprises (SMEs) through to multinational organisations, the case studies describe strategic approaches for the successful implementation of business systems, and provide engineers with insights into the design processes in each sector. Together, the case studies offer an insightful exploration of Africa's dynamic digital environment, and showcase how innovative engineering management applications are advancing local industries. They also offer important general lessons on fostering resilience and adaptability in an era of rapid technological progress. Digital Transformation in Engineering Management illustrates the immense benefits of technology for enhancing operations and maintaining competitiveness in a rapidly changing world. It is an essential guide for both practitioners and researchers seeking to understand the transformative potential of digitalisation.